Muslim Politics Between Sharia and Democracy - Kuru, Ahmet T. (Muslim Politics Review, 2022)
Out of 50 Muslim-majority countries around the world, only six are electoral democracies. This problem has multiple material and ideational causes. This essay focuses on one ideational factor: the dominant method of Islamic law. The essay explains how this method became dominant after the eleventh century and why it causes the incompatibility between sharia (Islamic law) and democracy. The essay suggests further research to be published in Muslim Politics Review and other journals about how to develop alternative Islamic legal methods, which would be open to rationalism and empirical observations.